Working Party 1: ASIC design, CAD tools & methodology - York, Trevor A. (Zielona Góra: Uniwersytet Zielonogórski)
A working party has been assembled, comprising academics from the six original participating institutions in JEP 0449, to suggest the curriculum for a course in "ASIC Design, CAD Tools and Methodology" at the Polish institutions of Wroclaw Technical University and Zielona Gora Higher College of Education.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka